Identification of prognostic and bone metastasis​‐related alternative splicing signatures in mesothelioma. (26th May 2021) - Huang, Runzhi; Zheng, Zixuan; Liu, Sijia; Yan, Penghui; Song, Dianwen; Yin, Huabin; Hu, Peng; Zhu, Xiaolong; Chang, Zhengyan; Liu, Yihan; Zhuang, Juanwei; Meng, Tong; et al.
Abstract: Mesothelioma (MESO) is an infrequent tumor derived from mesothelial cells of pleura, peritoneum, pericardium, and tunica vaginalis testis. Despite advancement in technologies and better understanding of tumor progression mechanism, the prognosis of MESO remains poor. The role of alternative splicing events (ASEs) in the oncogenesis, tumor metastasis and drug resistance has been widely discussed in multiple cancers. But the prognosis and potential therapeutic value of ASEs in MESO were not clearly studied by now. We constructed a prognostic model using RNA sequencing data and matched ASE data of MESO patients obtained from the TCGA and TCGASpliceSeq database. A total of 3, 993 ASEs were identified associated with overall survival using Cox regression analysis. Eight of them were finally figured out to institute the model by lasso regression analysis. The risk score of the model can predict the prognosis independently. Among the identified 390 splicing factors (SF), HSPA1A and DDX3Y was significantly associated with 43 OS‐SEs. Among these OS‐SEs, SNX5‐58744‐AT ( p = 0.048) and SNX5‐58745‐AT ( p = 0.048) were significantly associated with bone metastasis. Co‐expression analysis of signal pathways and SNX5‐58744‐AT, SNX5‐58745‐AT was also depicted using GSVA. Finally, we proposed that splicing factor (SF) HSPA1A could regulate SNX5‐58744‐AT (R = −0.414) and SNX5‐58745‐AT (R = 0.414) through the pathway "Class I MHC mediated antigen processing and presentation" (R = 0.400). In this way, tumorigenesis and bone metastasis of MESO were controlled. Abstract : Despite advancement in technologies and better understanding of tumor progression mechanism, the prognosis of Mesothelioma (MESO) remains poor. Alternative splicing events (ASEs) are widely reported in the tumorigenesis, metastasis and drug resistance of multiple cancers. Based on the results of this study, we proposed that splicing factor (SF) HSPA1A could regulate SNX5‐58744‐AT (R = ‐0.414) and SNX5‐58745‐AT through "Class I MHC mediated antigen processing and presentation" pathway and subsequently impact tumorigenesis and bone metastasis of MESO.